Probiotic lactic acid bacteria as a means of preventing in vitro urinary catheter colonization and biofilm formation - Mohamed Anwar Mahgoub; Aleya Abdel Gawad Abbass; Amani Farouk Abaza; Mohamed Shafik Shoukry (SpringerOpen, 2023)
Abstract Background Catheter-associated urinary tract infections (CAUTIs) are the most common infections found in healthcare facilities. Urinary catheters predispose the development of CAUTIs by destroying natural barriers and providing a source for infection and biofilm formation (BF). This study aimed to evaluate probiotic lactic acid bacteria (LAB) as a means of preventing in vitro urinary catheter colonization and BF. Methods Cross-sectional screening, followed by an experimental study, was conducted on 120 catheterized patients admitted to the urology department in a tertiary care hospital for 7 months. The isolated and identified uropathogens were tested for their antimicrobial susceptibility patterns by the disk diffusion method according to Clinical and Laboratory Standards Institute recommendations and examined for their ability to produce biofilms using a microtiter plate (MtP) assay. Five LAB (Lactobacillus acidophilus (L. acidophilus), Bifidobacterium bifidum (B. bifidum), L. paracasei, L. pentosus, and L. plantarum) were identified and examined for preventing in vitro colonization and BF of some isolated uropathogens on Foley urinary catheter surfaces. Results Of the 120 samples collected, 32.5% were found to be associated with CAUTIs. Of isolated organisms, 74.4% were gram-negative bacilli, while gram-positive cocci represented 14%, and only 11.6% were of the Candida species. About two-thirds of isolated uropathogens were biofilm formers. All five probiotic strains had inhibitory effects on the growth of all the uropathogens tested but with varying intensities according to the duration of application after 2, 4, and 6 days. Conclusions The prevalence of CAUTIs was high, and the predominant bacterial isolates were gram-negative bacilli. Many of the studied uropathogens were biofilm formers. The bacterial isolates had a higher prevalence of resistance to commonly prescribed antimicrobial agents. Probiotics have the potential to prevent in vitro urinary catheter colonization and inhibit BF. Pre-coating urinary catheters with probiotics is recommended after ensuring the safety of probiotics' use in vivo by carrying out further large-scale studies.